2019
DOI: 10.1002/ejp.1439
|View full text |Cite
|
Sign up to set email alerts
|

Associations between pain thresholds for heat, cold and pressure, and Pain Sensitivity Questionnaire scores in healthy women and in women with persistent pelvic pain

Abstract: Background The Pain Sensitivity Questionnaire (PSQ) is a self‐rating instrument developed as a time‐ and cost‐saving alternative to quantitative sensory testing (QST). The aims of the study were to assess (a) the associations between PSQ scores and QST in women with persistent pelvic pain and in pain‐free controls and (b) to what extent demographic variables and psychological distress influenced PSQ scores. Methods Fifty‐five healthy women and 37 women with persistent pelvic pain participated. All filled in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
3
22
1
Order By: Relevance
“…One limitation to this study is the generalizability of the present findings to pain sensitivity with respect to other sensory modalities (eg, cold pain, hot pain, or pressure pain). Evidence suggests a close relationship between thermal and mechanical pain sensitivity [63]. However, a comparative study across sensory modalities is necessary, and this issue is beyond the scope of the present study.…”
Section: Study Limitationsmentioning
confidence: 87%
“…One limitation to this study is the generalizability of the present findings to pain sensitivity with respect to other sensory modalities (eg, cold pain, hot pain, or pressure pain). Evidence suggests a close relationship between thermal and mechanical pain sensitivity [63]. However, a comparative study across sensory modalities is necessary, and this issue is beyond the scope of the present study.…”
Section: Study Limitationsmentioning
confidence: 87%
“…However, the cohort sizes from which stimulus response correlations with PSQ scores are published are limited (406 subjects in [16], 319 subjects in [18], 136 subjects in [17], 103 [19], 182 [20] and 331 [21]). More recently, Grundström et al (2019) demonstrated an association between PSQ total score and both temperature and pressure thresholds, not including the CPT, in a sample of 37 women with persistent pelvic pain and 55 control women, though associations were notably stronger in the chronic pain subgroup [22].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, they reported that pain hypervigilance was a predictor of temporal summation of heat pain, a marker of central sensitisation 36. Grundtrom et al reported a significant correlation between pain sensitivity measured using the Pain Sensitivity Questionnaire (PSQ)38 and PTTs measured at pelvic regions in patients with pelvic pain 39. Estimates of somatic awareness, such as SSA, are not commonly included as potential confounders in TMD research.…”
mentioning
confidence: 99%